2016
DOI: 10.21859/jhpm-06025
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the Relative Factors to the AIDS Prevention Based on “The Theory of Planned Behavior” in Nursing and Midwifery Students of Guilan University of Medical Sciences

Abstract: Introduction: AIDS is the most fatal infection diseases and the fourth cause of death in the world. Health education is the only way to prevent this. This study aims to determine the relative factors of the AIDS prevention based on "The Theory of Planned Behavior" in nursing and midwifery students of Guilan University of Medical Sciences. Methods: In this descriptive-correlation study, 104 first-year nursing and midwifery students of Guilan University of Medical Sciences were selected through census sampling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…49 The HIV, which leads to AIDS, is considered to attach to CD4+ (T4+) cells via the gp120 epithelial glycoprotein. 50,51 Plant lectin bind to glycoproteins through non-covalent interaction with particular hexose residues. 52 As a result, a lot of research has been done on the effects of plants on this disease In 1998, Yamasaki et al 53 showed notable inhibitory effects of Melissa officinalis against HIV-1 pathogenesis in MT-4 cells.…”
Section: Hivmentioning
confidence: 99%
“…49 The HIV, which leads to AIDS, is considered to attach to CD4+ (T4+) cells via the gp120 epithelial glycoprotein. 50,51 Plant lectin bind to glycoproteins through non-covalent interaction with particular hexose residues. 52 As a result, a lot of research has been done on the effects of plants on this disease In 1998, Yamasaki et al 53 showed notable inhibitory effects of Melissa officinalis against HIV-1 pathogenesis in MT-4 cells.…”
Section: Hivmentioning
confidence: 99%